Removal of Monovalent and Divalent Cations from Brine Water by Electrodialysis Using Modified Polyethersulfone Membranes - Zainab A. Khalaf; Sarah S. Mohammed Jawad (Tikrit Journal of Engineering Sciences, 2024)
In electrodialysis, an ion exchange membrane removes unwanted ions from wastewater and toxic metal ions from effluents. Montmorillonite-based modified "polyethersulfone membranes" have been studied as a potential small-scale electrodialysis approach for removing ions from wastewater. The study featured several steps, including solid polymerization, electrolyte balance, and removal of each component from the water. The study used three distinct “cation-exchange membranes (CEM)" types. The selected water body was diluted 100 times before being added to the electrodialysis cell in amounts of the center, cathodic, and anodic chambers, each containing 55, 30, and 40 mL. The initial pH for the real solutions of the water body was 7.16 at 25°C. Compared to "Sulfonated poly arylene ether sulfone (S-PESOS)" (23.23%) and Nafion® (35.34%), "hexamethylenediamine (HEXCl)" stands out as the only cross-linked material with significantly high-water content. When the membrane water content is too high, the membrane may lose its mechanical strength and cannot provide enough ionic conductivity. The semi-empirical model's parameters were estimated to simulate the elimination of Na+, K+, Ca2+, and Mg2+ by three membranes. HEXCl and S-PESOS were electrodialyzed and used to treat the serial dilution from the water with cationics. The removal rate gradually rose after the electrodialysis started.